Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1177/216507991306101004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Workplace Violence among Home Care Workers in a Consumer-Driven Home Health Care Program

Abstract: Nominal research has examined sexual harassment and workplace violence against home care workers within consumer-driven home care models such as those offered in Oregon. This study examined home care workers' experiences of violence while providing care to consumer employers, the patients who hire and manage home care workers. Focus groups and interviews were conducted in Oregon with 83 home care workers, 99 Oregon Department of Human Services (DHS) employees, and 11 consumer employers. Home care workers repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 17 publications
(3 reference statements)
2
67
1
Order By: Relevance
“…A total of 21 studies 2,3,6,7,9,11,13,15–23,30–34 were included for meta‐analysis. Twelve (57%) were conducted with US HHWs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 21 studies 2,3,6,7,9,11,13,15–23,30–34 were included for meta‐analysis. Twelve (57%) were conducted with US HHWs.…”
Section: Resultsmentioning
confidence: 99%
“…Parsing its prevalence rate into separate rates of physical violence and threat (ie, nonphysical violence in our review) was not feasible, and we needed to categorize it as physical violence. Five terms, sexual harassment, 6,7,9,11,19,31,32,34 sexual abuse, 9,16,17,19,22,23 sexual aggression, 32 sexual violence, 9,11 and sexual assault, 9,33,34 were used in the included studies to capture sexual violence. Although the first two tend to describe nonphysical, and the latter two physical sexual violence, this distinction was not always clear, and we categorized them into either category using our discretion based on the information in the article.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the union representing HC aides in Massachusetts has used collective bargaining to achieve paid orientation training for aides and an education program on topics including boundary setting and communication . Consumer‐directed aides in Washington State expressed a desire for similar training on assertiveness, communication, and “defining work boundaries” to help prevent violence and NIOSH has included a module on setting boundaries in its safety training materials for home health workers . Client intake offers an opportunity for agencies and home assessment professionals to formally educate clients on appropriate boundaries and limitations of the aide's role, as well as conduct a thorough assessment of client needs and safety concerns in the home.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that requests for tasks outside the job are a commonly-encountered issue for aides, and are ranked among the top job hazards for which they would like intervention. Both quantitative and qualitative analyses suggest that extra requests may be associated with OSH hazards and negative outcomes that have been previously identified as concerns in HC, including psychosocial stress, 15,21,22 conflict or abusive client behaviors, 9,[23][24][25][26][27] and injury and musculoskeletal pain. 9,28,29 The types of tasks requested, as identified in the qualitative analysis, reflect potential pathways to the negative outcomes found in the quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%